Knowledge and Attitude Can Increase Participation in Elderly Posyandu Visits - Bongga Linggi, Elmiana; Nurhanifah, Dewi; Ihsan Kamaruddin, Muh; Ode Novi Angreni, Wa; Suprapto, Suprapto; Kens Napolion (Window of Health : Jurnal Kesehatan, 2024)
The health and well-being of older adults are major concerns in improving the quality of life of the elderly population. The visit of the Elderly Posyandu is one of the programs designed to meet the health and social needs of older adults at the community level. Older adults' knowledge and attitudes towards using Posyandu Lansia services have an important role in determining their level of participation in the program. This study aims to analyze the knowledge and attitudes of older adults toward participation in Posyandu Lansia visits. A quantitative research method with a cross-sectional approach was used in this study. Respondents were selected based on purposive sampling, with as many as 86 respondents. The data were analyzed using the Fisher exact test. Fisher's exact statistical test results are known to be knowledge variables p value = 0.003, attitude is known p value = 0.002, meaning there is a correlation between knowledge and attitude towards the use of elderly posyandu visits. It can be concluded that efforts to improve the knowledge and attitudes of older adults towards the Posyandu Lansia program need to be increased through various education and health promotion strategies. Involving families, communities, and related parties in supporting the participation of older adults is also important. Thus, increased participation of older adults in the visit of the Elderly Posyandu can be achieved, thus positively impacting the overall health and well-being of older adults.